Perancangan dan Implementasi Aplikasi Bimbingan Konseling Berbasis Website di SMK Muhammadiyah 1 Kotabumi - Cahya Novita Sari; Ryan Aji Wijaya (Jurnal Sintaks Logika, 2026)
Obstacles in efficient data documentation and limited interaction between guidance and counseling teachers and students are the main obstacles in providing guidance and counseling services in schools. This research focuses on the design and implementation of a website-based guidance and counseling application at SMK Muhammadiyah 1 Kotabumi to optimize data management and consultation services. The development of this system applies the (RAD) method, which prioritizes speed and flexibility through the stages of planning, iterative development (design, development, testing, and user review), and deployment. The system architecture is modeled using Unified Modeling Language (UML), including use case diagrams and activity diagrams that detail the operational flow from the login process to systematically accessing guidance reports. This application was built using the PHP programming language and MySQL database. The results of the study indicate that this centralized platform successfully integrates counseling history, achievement data, and student violations in real-time. Based on Black Box testing, all navigation functions and application features are declared to run well without technical problems. The implementation of this system is expected to improve the effectiveness of guidance and counseling services, facilitate monitoring of student behavior, and ensure the security of counseling data at SMK Muhammadiyah 1 Kotabumi.